Viabilidade econômica dos créditos de CO2 da cana-de-açúcar na produção de aguardente artesanal - Alves, Lázaro Quintino (2009)
One of the greatest challenges of humankind is sustainable production with clean development mechanisms (CDM) in order to reduce the emission of greenhouse gases and provide a better world to future generations. In this context, sugarcane brandy production should be considered an agroindustrial complex which is capable of contributing to carbon sequestration. As a traditional activity in Brazil, it also generates jobs and wealth. The purpose of this research was to economically evaluate the potentialities of carbon emission and sequestration balance of sugarcane in brandy production, and verify whether the sale of carbon credits could provide additional income and increase the gross revenue in each harvest. An attempt was made to understand the history of sugarcane, a primary source of brandy, and it was found that its history is mixed with Brazil s own history, even today. We studied aspects of carbon balance, economical aspects, and the amount of trading of carbon and brandy, from April to October 2008, to assess the economic viability of sugarcane carbon sequestration and brandy. To determine the carbon sequestration balance in the sugarcane brandy agribusiness a survey was made of all the carbon sequestered by the sugarcane plantation, and also of the carbon emission during all the stages of the productive process. All this survey was based on data obtained from scientific papers. Carbon trading can be done at BM&F (Futures and Commodities Exchange) or directly by the companies that to lower their pollution levels. It is understood that the best way for small producers to engage in carbon trading is through a cooperative of CO2 trading. Alongside with the search for production of clean energy, the correctly managed sugarcane cultivation can contribute to agriculture sustainability as both a great carbon sequesterer and an additional source of income for brandy producers.